Influenza d virus infection in herd of cattle, Japan - Murakami, S.; Endoh, M.; Kobayashi, T.; Takenaka-Uema, A.; Chambers, J. K.; Uchida, K.; Nishihara, M.; Hause, Benjamin M.; Horimoto, T. (My University, 2016)
Although the provisionally named influenza D virus was first isolated as an influenza C–like virus from pigs with respiratory illness in Oklahoma in 2011 (1,2), epidemiologic analyses suggested that cattle are major reservoirs of this virus (3) and the virus is potentially involved in the bovine respiratory disease complex. The high rates of illness and death related to this disease in feedlot cattle are caused by multiple factors, including several viral and bacterial co-infections. Influenza D viruses were detected in cattle and pigs with respiratory diseases (and in some healthy cattle) in China (4), France (5), Italy (6), among other countries, indicating their wide global geographic distribution. Although the influenza D virus, like the human influenza C virus, is known to use 9-O-acetylated sialic acids as the cell receptor (2,7), its zoonotic potential is undefined because of limited research (1,8). We report influenza D virus infection in a herd of cattle in Japan.
Citation: Murakami, S., Endoh, M., Kobayashi, T., Takenaka-Uema, A., Chambers, J. K., Uchida, K., . . . Horimoto, T. (2016). Influenza d virus infection in herd of cattle, Japan. Emerging Infectious Diseases, 22(8), 1517-1519. doi:10.3201/eid2208.160362